Multi-objective optimization aided to allocation of vertices in aesthetic drawings of special graphs - Varoneckas, Audrius; Žilinskas, Antanas; Žilinskas, Julius (Nonlinear Analysis: Modelling and Control, 2013)
A problem of drawing specific graphs is considered emphasizing aesthetic appeal of the visualization. We focus on graphs related to the management of business processes. A particular problem of the aesthetic drawing is considered where the aesthetic allocation of vertices is aimed. The problem is stated as a problem of bi-objective optimization where the objectives are the length of connectors and the compatibility of the sequence flows with the favorable top-down, left-right direction. An algorithm based on the branch-and-bound approach is proposed.